Challenges in Writing Academic Papers for International Publication Among Indonesian Graduates Students - Azizah, Umu Arifatul; Budiman, Asep (Universitas Islam Negeri (UIN) Syekh Wasil, Kediri, Indonesia, 2017)
The aims of this study are to investigate the problems and challenges of university students in writing English scholarly article for an international journal and to elaborate their perceptions toward the importance of writing for the publication. Furthermore, it also explores the certain needs to support their skills in the process of writing the article.The investigation involves 20 students from one of the universities in Indonesia. It uses a questionnaire consisted of 24 items to understand the students‟ problems and perceptions of the issues in relation to writing for the academic publication in English. The findings of this study indicate that claiming knowledge was the most difficult aspect in writing the article. On the other hand, students agree that writing for international publication is considered as a crucial action in academic field, and henceforth, they needs to have university‟s support to prepare students‟ writing. Finally, some suggestions related to students‟ problem in writing for international publicationare are offered.